Sistem Pondok Pesantren Tahfizh Al-Qur’an Anak-anak Yanbu’ Alqur’an Kudus Jawa Tengah (THUFULA, 2015)
The paper of research institutional traditional system (pesantren) forchildern age 6-12 Th in Yanbu’ Al-Qur’an Kudus Central Java. The fist programis memorization of the Qur’an 30 juz, and learning is basic shool (MI) madrasatahfiz al-Qur’an. Educational Islamic system in institutional traditional include ofteacher, students (santri), materials or curriculum, methods of memorization ofal-Qur’an, and insfastructure and environment education is dominant factor insuccesfull system education especially in pesantren.